Analisis Preferensi Konsumen Dalam Pengambilan Keputusan Keputusan Pada Penggunaan Go-Jek Sebagai Alat Transportasi (Studi Kasus Mahasiswa Brawijaya Malang) - IVAN MUN`IM VARADIAN (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Transportation became one of the important supporting factor in daily activities especially in urban areas. The regularity of the city can be created if it has good transport, this happens because transportation is a tool in driving development in the urban areas. In addition, transportation also is an infrastructure for human movement or goods incurred due to activity in urban areas. Indonesian. Malang became one of the more experienced congestion on some roads. At the time of an increasingly modern consumers like to have transportation services that are more practical and innovative. Recently transformed into a taxi-taxi with the birth of professional Go-Jek. Many have welcomed the presence of motorcycle taxis online as an option the model different transport services, but with the taxi pengkolan who did not receive an online presence where they presume that they took a taxi to their consumers online. The dispute between the two sides can not be bending to refer to an online attack action in doing the taxi pangkolan. The purpose of this research is to find out what factors that shape consumer preference in the use of Go-Jek as means of transportation at the University of Brawijaya Malang, because at the University a lot of demand for services Go-Jek. The results of this research are cost, reliability and security of a significant effect, while ease of influential not significantly to consumer preference. Keywords: Consumer Preference, Go-Jek, Analysis Of Factors.